Rancang Bangun Mesin Perajang Singkong dengan Pendorong Pegas - Venditias Yudha; Nanang Nugroho (Universitas Muhammadiyah Yogyakarta, 2020)
The home industry business of cassava chips on Jogonalan, Klaten was using the manual tools in the process of slicing raw cassava. The cassava cutting machine was an alternative solution for the businessman to increase productivity in the process of producing cassava chips. This machine functions as a cassava cutting in the raw material for making chips. The purpose of this design is to plan a cassava cutting machine with a safe and efficient construction in its application. The machine design method refers to the Pahl and Beitz concept. The planning and design process into the following main phases: Planning and task clariﬁcation, conceptual design, embodiment design, and detail design. Analysis of the motion mechanism and calculation of engine elements were used to determine the power specification and capacity of the machine. The planned capacity of the cassava cutting machine is 80kg/hour with a motor power of 0.25 hp, the final rotation of 210 rpm. The results of the technical analysis on the main part of the cassava cutting show that the power capacity of the electric motor, transmission system and frame construction on the machine was safe.